2017
DOI: 10.1007/s00373-017-1807-2
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of Cliques for (m, n)-Colored Mixed Graphs

Abstract: An (m, n)-colored mixed graph is a mixed graph with arcs assigned one of m different colors and edges one of n different colors. A homomorphism of an (m, n)-colored mixed graph G to an (m, n)-colored mixed graph H is a vertex mapping such that if uv is an arc (edge) of color c in G, then f (u)f (v) is also an arc (edge) of color c. The (m, n)-colored mixed chromatic number, denoted χ m,n (G), of an (m, n)-colored mixed graph G is the order of a smallest homomorphic image of G. An (m, n)-clique is an (m, n)-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…It is therefore easy to check whether a given oriented graph is an oclique. On the other hand, it is NP-complete to decide whether a given graph can be oriented to be an oclique [1].…”
Section: Preliminary Results: Oriented Cliquesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore easy to check whether a given oriented graph is an oclique. On the other hand, it is NP-complete to decide whether a given graph can be oriented to be an oclique [1].…”
Section: Preliminary Results: Oriented Cliquesmentioning
confidence: 99%
“…We claim the vertices of G − z are configured as in one of the two partially oriented graphs in Figure 9 where the unoriented edges are oriented so that each of A v 2 and A v 2 contains an element from Z. By the previous argument, u 1 and v 1 (respectively u 2 and v 2 ) have a pair of common neighbours. Since A v 1 (respectively A v 2 ) contains a copy of Z ∈ Z (respectively Z ∈ Z), these common neighbours must either be adjacent or are the ends of a 2-dipath.…”
Section: Oriented Colourings Of Graphs With Maximum Degree Threementioning
confidence: 98%
See 1 more Smart Citation
“…For simple undirected graphs, the absolute and relative clique numbers coincide which is not the case when (m, n) = (0, 1) [2].…”
Section: Introductionmentioning
confidence: 91%
“…That is, no two distinct vertices of a relative clique can be identified under any homomorphism. The (m, n)-relative clique number ω r(m,n) (G) of an (m, n)-colored mixed graph G is the cardinality of a largest relative (m, n)-clique of G. Bensmail, Duffy and Sen [2] showed that ω a(m,n) (G) ≤ ω r(m,n) (G) ≤ χ m,n (G).…”
Section: Introductionmentioning
confidence: 99%